Circulating CD14+CD16− classical monocytes do not associate with a vulnerable plaque phenotype, and do not predict secondary events in severe atherosclerotic patients. (February 2019) - Meeuwsen, John A.L.; de Vries, Judith J.; van Duijvenvoorde, Amerik; van der Velden, Saskia; van der Laan, Sander W.; van Koeverden, Ian D.; van de Weg, Sander M.; de Borst, Gert J.; de Winther, Menno P.J.; Kuiper, Johan; Pasterkamp, Gerard; Hoefer, Imo E.; et al.
Abstract: Aims: Mouse studies have established distinct monocyte subtypes that participate in the process of atherosclerotic lesion formation. The pro-inflammatory Ly6C high monocyte subtype actively contributes to murine plaque progression and destabilization. Also in humans, different peripheral monocyte subtypes have been identified, of which the CD14 + CD16 − classical monocyte is suggested to display similar pro-atherosclerotic properties as the murine Ly6C high subtype. We aimed to investigate if circulating CD14 + CD16 − classical monocytes associate with characteristics of a vulnerable carotid atherosclerotic plaque and if they associate with the risk of secondary adverse manifestations of atherosclerotic disease. Methods and results: We enrolled 175 carotid endarterectomy patients of the Athero-Express biobank in our study. Just prior to surgical procedure, blood was collected and peripheral blood mononuclear cells were isolated. Characterization of monocyte subsets was performed by flow cytometry. Plaque characteristics were semi-quantitatively scored for the presence of fat, collagen, intraplaque hemorrhage and calcification. Vessel density, smooth muscle cells and macrophages were assessed quantitatively on a continuous scale. All features of a vulnerable plaque phenotype, including low amounts of collagen and smooth muscle cells, and increased fat content, vessel density, intraplaque hemorrhage and plaque macrophages were not significantly associated with differential levels of peripheral classical CD14 + CD16 − monocytes or other monocyte subsets. Using Cox regression models to evaluate the prognostic value of circulating monocyte subtypes, we found that total counts of peripheral monocytes, as well as CD14 + CD16 − classical and other monocyte subtypes were not associated with the risk of secondary cardiovascular events during 3 years follow-up. Conclusion: Circulating classical CD14 + CD16 − monocytes do not associate with specific vulnerable plaque characteristics. In addition, they do not predict secondary adverse manifestations. This suggests that in patients with established carotid artery disease, the circulating monocytes do not reflect plaque characteristics and have no value in identifying patients at risk for future cardiovascular events. Highlights: Circulating monocyte subtypes do not associate to plaque phenotype in advanced atherosclerotic lesions. Circulating classical monocytes do not associate to a vulnerable plaque phenotype. Circulating monocyte subtypes do not associate future events.